Ecofeminism in Baduy Customary Practices: Women as Ecological Buffers and Customary Parents - Prayitno Prayitno; Taofik Hidayat; Raudhatul Hasanah Lie (Al-Makki Publisher, 2026)
Feminism is a theoretical approach and critical school of thought that aims to examine the inequality of gender-based power relations in various dimensions of social life. Ecofeminism emerged as a development of feminist thought that links the oppression of women with the exploitation of nature. This perspective holds that the logic of domination that positions nature as an object to be controlled and exploited is in line with the patriarchal perspective that demeans women. When feminism and ecofeminism are applied in the context of indigenous communities in Indonesia, women's experiences need to be understood contextually and in layers. In the Baduy Indigenous Community, the relationship between men and women in Baduy society is complementary, without patterns of domination or placing women in a subordinate position. This study aims to understand the role of Baduy women as ecological actors who play a central role in sustainability. By combining the results of previous research and an ecofeminist perspective, this paper attempts to view the Baduy as a concrete example of indigenous ecofeminism. This research is a qualitative ethnographic study with a descriptive and analytic approach. The main focus is to explore how the role of Baduy women in ecological activities is read from an ecofeminist perspective. The results show that Baduy women are the backbone of their indigenous community's food and economic security, carrying out vital roles that are closely integrated with spiritual beliefs and environmental sustainability. Baduy women, through their adherence to Pikukuh customary law and daily interactions that respect nature.